Violent crime and modernization in Colombia - Bouley, Eugene E. (Crime, law and social change, 1995)
This paper assesses violent crime in Colombia by focusing on police arrest data from 1938 to 1967. Social and political conditions provide the cultural context from which the effects of modernization on crime are examined. Shelley's modermization perspective claims that violent crime increases when a country modernizes, but property crimes increase after relative wealth and prosperity are achieved. Regression results support Shelley's perspective for the crimes of robbery and theft, whereas her theory gamered weaker support for the crimes of homicide and assault. Theoretical implications for modernization theory in light of the findings are discussed.